Quasi-Rational R&D Behavior in an Environment with Fundamental Uncertainty - Anne-Kathrin Dimmig; Mathias Erlei (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2012)
The objective of our paper is to study R&D investments and pricing behavior in an environment with fundamental uncertainty. We designed a multi-period experiment in which each period consisted of two stages, an R&D phase and a pricing stage. Participants in the experiment had almost no information about the underlying functions, parameters, and probabilities. Subjects' behavior in the fundamentally uncertain environment of our experiment may best be characterized as some kind of procedural rationality which we call quasi-rationality. Pricing decisions are particularly close to equilibrium values. Although we do find some hints of the existence of behavioral effects in R&D decisions, only reinforcement effects are significant across both treatments and different model specifications. The introduction of patents has only a minor impact on R&D behavior. Overall, subjects learn to adapt remarkably well to a rather complex and fundamentally uncertain environment.
Keywords: C90; D81; L10; O31; 330; bounded rationality; duopoly; innovation; experiment; R&D competition